Economic expenditure in low-cost fitness centers: Differences according to the loyalty and characteristics of the client - J. García Fernández; P. Gálvez Ruíz; A. Bernal García; L. Vélez Colón (Universidad de Murcia, 2016)
Thegrowth in thenumber of fitness centers and theirclients, thestudysoughtto examine and understandthebehavior of consumers of these sport organizations. Therefore, theobjective of thisstudywastoanalyzefordifferences in economicexpendituresbasedoncustomerloyalty and customerprofile in low-cost fitness centers. Thesamplewascomposed of 8462 clients of which50.9% (n=4303) werewomen and 49.1% (n=4159) men. A descriptiveanalysiswasconductedwiththevariancetoaddresstheobjective of thestudy. Theprincipleresultsindicatesignificantdifferences in regardstotheeconomicexpendituresaccordingtogender, age, longevitywiththeorganization and behaviorintentions as measuredwith Net Promoter Score. Thesefindings are of importantrelevanceoffering a detailedunderstanding of clients and variables whichshould be appropriatelymanagedtoincreasetheclients' expenditure.